Naive Bayes Classification for Construction Workforce Requirement Prediction - Nuzaima Agustari; Roberto kaban; Safarul Ilham (JCEIT: Journal of Computer Engineering and Information Technology, 2026)
The determination of construction worker requirements at the Langkat Regency Public Works and Spatial Planning Office (PUPR) is still conducted manually, often resulting in inaccurate workforce allocation and inefficiencies in project implementation. Therefore, a data-driven approach is needed to improve prediction accuracy. This study aims to apply the Naive Bayes algorithm to predict construction worker needs based on historical project data. This research uses a quantitative approach with a classification method. The dataset includes variables such as project type, budget, duration, and previous labor usage. Data processing involves preprocessing, training, and testing, with a data split of 80% for training and 20% for testing. The Naive Bayes model is then evaluated using accuracy, precision, recall, and F1-score metrics. The results show that the Naive Bayes algorithm achieves an accuracy of 86.7%, precision of 84.5%, recall of 87.2%, and F1-score of 85.8%. The model is capable of classifying workforce needs into low, medium, and high categories effectively. In conclusion, the Naive Bayes algorithm provides a reliable and efficient method for predicting construction worker requirements, supporting better decision-making and workforce planning at the Langkat Regency PUPR Office. REFERENCES Agustina, F. D., Arif, M., & Ahmad, S. (2025). Systematic Literature Review atas Kinerja Algoritma KNN, Naïve Bayes, dan Decision Tree pada Berbagai Studi Prediksi dan Klasifikasi. Jurnal Jawara Sistem Informasi, 3(1). Andika, A., Syarli, S., & Sari, C. R. (2022). Data Mining Klasifikasi Kelulusan Mahasiswa Menggunakan Metode Naïve Bayes. 4(1), 423–428. Anggreni, A., Hakim, A., Rahman, A., & Dinata, M. I. (2026). Klasifikasi Partisipasi Pemilih pada Pemilihan Walikota Bima Tahun 2024 Menggunakan Metode Naive Bayes Classifier. Jurnal Sains Natural, 4(1), 1–13. Azhar, S., Informatika, J. T., & Teknik, F. (2019). Decision Tree Dalam Memprediksi Kelulusan. (September), 1–8. Azizah, S. N. (2025). Kecerdasan Buatan dalam Pengelolaan SDM: Tantangan dan Peluang. Penerbit NEM. Fatimah, S., Adys, A. K., & Rahim, S. (2021). Strategi Dinas Pekerjaan Umum dan Penataan Ruang Dalam Perbaikan Infrastruktur Jalan di Kabupaten Bone. KIMAP: Kajian Ilmiah Mahasiswa Administrasi Publik, 2(4), 1412–1426. Fitria, R. (2025). Perancangan Sistem Informasi Akademik Berbasis Website Di Sdn 21 Tulang Bawang Udik Kabupaten Tulang Bawang Barat. Hadi, R., Pivin, N. L. G., Kusuma, I. G. N. A., Saryanti, I. G. A. D., & Novayanti, P. D. (2025). Analisis Perbandingan Algoritma K-Nearest Neighbor (Knn) Dan Support Vector Machine (Svm) Dalam Klasifikasi Data Perbankan. Jurnal Informasi Dan Komputer, 13(01), 167–173. Jariah, A., & Mufarrohah, H. (2025). Penerapan Probabilitas Bayes Dalam Pengambilan Keputusan Akademik Siswa. AL-BAHTS: Jurnal Ilmu Sosial, Politik, Dan Hukum, 2(3), 28–40. Kamuri, K. J., Manongga, I. R., Anabuni, A. U., Benu, Y. S. I. P., & Siahaan, M. Y. (2025). Manajemen Sumber Daya Manusia (MSDM) Era Digital. Penerbit Buku Indonesia (PBI). Macfud, A. Z., Kusuma, A. P., & Puspitasari, W. D. (2023). Analisis Algoritma Naive Bayes Classifier ( Nbc ). 7(1), 87–94. Mahbubi, M. F. (2025). Efektivitas Tugas Kelurahan Di Bidang Pemberdayaan Masyarakat Kelurahan Pekan Kuala Kecamatan Kuala Kabupaten Langkat. Mamuriyah, N., Haeruddin, H., & Hero, H. (2024). Pembangunan Chatbot Interaktif Dengan Menggunakan Algoritma Naive Bayes. Informatika: Jurnal Teknik Informatika Dan Multimedia, 4(2), 82–94. Mardizal, J. (2025). Manajemen Proyek Konstruksi: Strategi Dan Teknik Untuk Sukses. Rajawali Pers. Masgode, M. B., Hidayat, A., Laksmi, I. A. C. V., Triatmika, I. N. A., Puspayana, I. P. A. I., Iskandar, A. A., Syarif, M., Rachman, R. M., Herlambang, A. R., & Dirgantara, A. (2024). Dinamika Industri Konstruksi di Indonesia. Tohar Media. Mita Febri Anika. (2022). Peran Bidang Program Pada Dinas Pupr Kabupaten Aceh Barat Dalam Pembangunan Jalan. Jurnal Ilmiah Teknik Unida, 3(1), 37–41. https://doi.org/10.55616/jitu.v3i1.205 Ningsih, W., & Abdullah, F. (2021). Analisis Perbedaan Pencari Kerja dan Lowongan Kerja Sebelum dan Pada Saat Pandemi Covid-19 di Kota Malang. Journal of Regional Economics Indonesia, 2(1), 42–56. https://doi.org/10.26905/jrei.v2i1.6181 Pangestu, A., Geni, B. Y., & Dinanti, P. A. (2025). Perancangan Sistem Prediksi Kesempatan Kerja Mahasiswa Berdasarkan Profil Akademik dan Pengalaman Kerja. JATI (Jurnal Mahasiswa Teknik Informatika), 9(6), 9731–9738. Prastyo, E. H. A., Suhartono, S., Faisal, M., Yaqin, M. A., & Firdaus, R. A. J. (2024). Naive Bayes Classification Untuk Prediksi Cacat Perangkat Lunak. JIPI (Jurnal Ilmiah Penelitian Dan Pembelajaran Informatika), 9(2), 782–791. Rachman, A., Arbi, R., Giola, Y., Zubeidi, S., & Araujo, A. L. (2024). Perencanaan sumber daya manusia. Tohar Media. Rismayadi, D. A., SI, S., Kom, M., Faira, F., Adjani, K., Kom, S., & Kom, M. (2025). Algoritma dan Data Driven Decision Making dalam Bisnis. Alungcipta. Sembiring, T. B., & SH, M. (2022). Pengelolaan Daerah Aliran Sungai: Studi Di Kawasan Das Kabupaten Langkat. Penerbit Adab. Shelvira, H. P. (2025). Perbandingan Model Na¨ Ive Bayes Dan Random Forest Dalam Prediksi Klasifikasi Masa Studi Sarjana Matematika Universitas Lampung. Shoheh, M. (2025). Pengantar Ilmu Futurologi. Penerbit A-Empat. Sihite, H. M. (2024). Implementasi Metode Naïve Bayes Terhadap Minat Masyarakat Rantau Utara Memilih Pakai Kartu Sim Telkomsel.